Disparities in Health Communication of the Groups of Mosques in Responding to the Covid-19 Pandemic in Banjarmasin, South Kalimantan - Bachruddin Ali Akhmad (Ikatan Sarjana Komunikasi Indonesia, 2020)
The use of health communication in the group of Nahdlatul Ulama (NU) mosques and the group of Muhammadiyah mosques in the midst of the Covid-19 pandemic in Banjarmasin City is inseparable from the background of the two religious organizations. In responding to the government’s call for mosques not to hold Friday prayers to contain the transmission of Covid-19, the group of Muhammadiyah mosques made persuasive, cautious and rational approaches to convey the message of the call to the congregation. On the other hand, the message of the call conveyed by the group of NU mosques to the congregation is coercive and tends to cause fatal or radical attitude. This study recommends that the group of NU mosques be united to manage an organization functioning as a basis, umbrella, and command. This way more effective and controllable communication among NU mosques can be created to resolve internal differences while conveying communication messages. The conclusion and recommendation are based on the results of the research conducted through qualitative approaches using data collection techniques covering observation and unstructured interviews to obtain indepth and pure data. Qualitative data analysis was conducted before, during and after a field research.